Genetic characterization and evidence for multiple reassortments of rotavirus A G3P[3] in dogs and cats in Thailand - Chamsai, Ekkapat; Charoenkul, Kamonpan; Udom, Kitikhun; Jairak, Waleemas; Chaiyawong, Supassama; Amonsin, Alongkorn (Frontiers in Veterinary Science, 2024)
Rotavirus A (RVA) causes gastroenteritis in humans and animals. The zoonotic potential of RVA has been reported and raises major concerns, especially in animal-human interface settings. The study aimed to characterize and investigate the genetic diversity among RVAs in dogs and cats in Thailand. We collected 572 rectal swab samples from dogs and cats in Bangkok animal hospitals from January 2020 to June 2021. The one-step RT-PCR assay detected RVAs in 1.92% (11/572) of the samples, with 2.75% (8/290) in dogs and 1.06% (3/282) in cats. Two canine RVA and one feline RVA were subjected to whole genome sequencing. Our results showed that all three viruses were identified as RVA genotype G3P [3]. The genetic constellation of RVAs is unique for different species. For canine RVAs is G3-P[3]-I3-R3-C3-M3-A9-N2-T3-E3-H6, while Feline RVA is G3-P[3]-I8-R3-C3-M3-A9-N3-T3-E3-H6. Notably, both canine and feline RVAs contained the AU-1 genetic constellation with multiple reassortments. The results of phylogenetic, genetic, and bootscan analyses showed that canine RVAs may have reassorted from dog, human, and cat RVAs. While feline RVA was closely related to RVAs in humans, bats, and simians. This study provided genetic characteristics and diversity of RVAs in dogs and cats and suggested possible multiple reassortments, suggesting the zoonotic potential of the viruses. Thus, public health awareness should be raised regarding the zoonotic potential of RVAs in dogs and cats.Further studies on RVAs on a larger scale in dogs and cats in Thailand are needed.